2016
DOI: 10.18632/oncotarget.8642
|View full text |Cite
|
Sign up to set email alerts
|

Optimal surgical strategy for hepatocellular carcinoma with portal vein tumor thrombus: A propensity score analysis

Abstract: ObjectivesThe optimal surgical resection method for hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) that maximizes both safety and long-term outcome has not yet been determined. The aim of this study was to compare the clinical outcomes following peeling off versus en bloc resection for PVTT.MethodsFrom 2005 to 2012, 252 patients with HCC and type I/II PVTT who underwent hepatic resection were divided into two groups according to whether they received en bloc resection (n = 113) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
4
28
1
Order By: Relevance
“…A systematic review of hilar cholangiocarcinoma data similarly noted that perioperative outcomes among patients undergoing curative resection with or without portal vein reconstruction were markedly different . However, while Chok et al noted a modest increase in morbidity among HCC patients who underwent en bloc resection and reconstruction of the PV, a similar study examining patients with hepatocellular carcinoma noted no difference in adverse perioperative events among patients who underwent hepatectomy with or without concomitant en bloc PV resection . In the current study, perioperative complications were common as nearly one‐half of patients experienced at least one complication.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…A systematic review of hilar cholangiocarcinoma data similarly noted that perioperative outcomes among patients undergoing curative resection with or without portal vein reconstruction were markedly different . However, while Chok et al noted a modest increase in morbidity among HCC patients who underwent en bloc resection and reconstruction of the PV, a similar study examining patients with hepatocellular carcinoma noted no difference in adverse perioperative events among patients who underwent hepatectomy with or without concomitant en bloc PV resection . In the current study, perioperative complications were common as nearly one‐half of patients experienced at least one complication.…”
Section: Discussionmentioning
confidence: 42%
“…A systematic review of hilar cholangiocarcinoma data similarly noted that perioperative outcomes among patients undergoing curative resection with or without portal vein reconstruction were markedly different. 27 However, while Chok 29 In the current study, perioperative complications were common as nearly one-half of patients experienced at least one complication. The odds of a perioperative complication were comparable, however, among patients who did and did not undergo a major vascular resection (OR 0.68, 95%CI, 0.33-1.45, P = 0.32).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been considered contraindicated by many institutions, including the BCLC system [41] . However, many studies, particularly those from the Asian centers, have reported hepatic resection to be safe and effective for patients with portal vein invasion [28,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] [ Table 3]. The median 1-, 3-and 5-year overall survival rates for patients with all forms of portal vein invasion treated with surgery were 61.0%, 32.9% and 27.0% respectively.…”
Section: Surgerymentioning
confidence: 99%
“…As in China, more than 50% new developed cases occurred in this country alone, which usually arises as a result of a chronic liver disease, especially hepatitis B virus (HBV) related. Due to its greatly invasive malignant features, HCC has a characteristic propensity to invade into portal vein, or to develop intra-hepatic metastasis, which was regarded as one of the most adverse prognostic factors [ 3 ]. Although several staging systems have been proposed for determining the stage and prognosis of HCC, no consensus exists on the best classification system [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Barcelona clinic liver cancer (BCLC) staging system, most UICC stage T3 HCC cases are classified as being Stages B or C, therefore transarterial chemoembolization (TACE) or Sorafenib, rather than hepatic resection (HR) are recommended as the optimal therapy for patients in these stages in Europe or North America [ 5 ]. However, therapy strategy may be a little different in Asian-Pacific areas [ 2 , 3 , 6 , 7 ]. Until now, it seems difficult to reach a common consensus on the indication of HR for HCC patients worldwide.…”
Section: Introductionmentioning
confidence: 99%